Investigating the Relationship Between Glucagon-Like Peptide-1 Receptor Agonist Use and Incidence of Vertebral Fractures in Female Patients Aged Over 50 Years With Osteoporosis - Kyle Stump; Sean Kelleher; Stephan Aynaszyan; Samuel Ricci; Theresa Pazionis (Clinical Spine Surgery, 2026)
Study Design: Retrospective cohort. Objective: To investigate the relationship between GLP-1 receptor agonist exposure and incidence of vertebral fracture and surgical intervention for these injuries in patients with osteoporosis. Summary of Background Data: Vertebral fractures are relatively common in patients with osteoporosis and frequently result in substantial morbidity, such as persistent pain and functional deficit. Although primarily indicated for the management of type 2 diabetes mellitus and obesity, glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have demonstrated positive effects on bone mineral density (BMD) in the lumbar spine. However, it remains unknown if this effect translates to positive clinical outcomes for patients with osteoporosis. Methods: This study utilized the TriNetX database to identify female patients aged over 50 years diagnosed with osteoporosis without a current pathologic fracture within the 10-year period ended January 1, 2025. The study group included patients with a history of GLP-1 RA use after osteoporosis diagnosis compared with a control group with no GLP-1 RA exposure. Cohorts were propensity-matched based on baseline demographic characteristics, BMI, HbA1c, eGFR, medical comorbidities, osteoporotic medication use, and serum calcium, phosphate, and vitamin D levels. Primary outcomes included incidence of vertebral collapse and vertebral augmentation within the 10-year study period. Results: There were 56,142 matched pairs. The rate of vertebral fracture in the experimental group was ∼1.9% compared with 4.3% in the control group (RR: 0.434, 95% CI: 0.404–0.467, P